2004
DOI: 10.1139/g03-101
|View full text |Cite
|
Sign up to set email alerts
|

Linkage mapping of powdery mildew and greenbug resistance genes on recombinant 1RS from 'Amigo' and 'Kavkaz' wheat–rye translocations of chromosome 1RS.1AL

Abstract: Cultivated rye (Secale cereale L., 2n = 2x = 14, RR) is an important source of genes for insect and disease resistance in wheat (Triticum aestivum L., 2n = 6x = 42). Rye chromosome arm 1RS of S. cereale 'Kavkaz' originally found as a 1BL.1RS translocation, carries genes for disease resistance (e.g., Lr26, Sr31, Yr9, and Pm8), while 1RS of the S. cereale 'Amigo' translocation (1RSA) carries a single resistance gene for greenbug (Schizaphis graminum Rondani) biotypes B and C and also carries additional disease-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
19
0
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 35 publications
2
19
0
3
Order By: Relevance
“…Since the 1990s, due to its single origin, the 1RS chromosome arm derived from Petkus rye has not provided protection against the prevalence of virulent pathogens (Shi et al, 2001; Ren et al, 2009). So far, only a few other sources of 1RS were transferred into wheat (Ko et al, 2002; Mater et al, 2004; Ren et al, 2009, 2012; Molnár-Láng et al, 2010; Yang et al, 2014; Li et al, 2016a,b; Qi et al, 2016), and not every new translocation line could be used in wheat breeding programs (Ren et al, 2012). For more efficient use of the T1RS.1BL translocation in wheat breeding, Ren et al (2012) suggested introduce a large amount of new genetic variation from many different rye sources into wheat.…”
Section: Introductionmentioning
confidence: 99%
“…Since the 1990s, due to its single origin, the 1RS chromosome arm derived from Petkus rye has not provided protection against the prevalence of virulent pathogens (Shi et al, 2001; Ren et al, 2009). So far, only a few other sources of 1RS were transferred into wheat (Ko et al, 2002; Mater et al, 2004; Ren et al, 2009, 2012; Molnár-Láng et al, 2010; Yang et al, 2014; Li et al, 2016a,b; Qi et al, 2016), and not every new translocation line could be used in wheat breeding programs (Ren et al, 2012). For more efficient use of the T1RS.1BL translocation in wheat breeding, Ren et al (2012) suggested introduce a large amount of new genetic variation from many different rye sources into wheat.…”
Section: Introductionmentioning
confidence: 99%
“…Such genetic vulnerability was largely caused by wide deployment of 1BL•1RS translocations in which the 1RS chromosome arm was mainly from one variety, i.e., ''Petkus'' rye (Villareal et al 1998;Lelley et al 2004). So far, only a few sources of 1RS were the progenitors of 1BL•1RS translocation in wheat worldwide (Lukaszewski 1990;Kim et al 2004;Mater et al 2004;Ren et al 2009). Therefore, it is critical to search for and introduce new elite alien genes to increase the genetic diversity of common wheat by development of more 1BL•1RS translocations (Ren et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Paldanghomil in Korea. A 1AL.1RS translocation cultivar, Amigo, which is derived from the 1RS arm of rye cultivar Insave, has been a source in some North American wheat cultivars due to its resistance against powdery mildew, greenbug, stem rust, and wheat curl mite (Zeller and Fuchs, 1983;Zeller and Hsam, 1983; Con-Diversity resistance to stripe rust in 1RS 10 ner et Rabinovich, 1998;Mater et al, 2004). Another 1AL.1RS translocation was selected in the 1990s (Porter et al, 1991(Porter et al, , 1994.…”
Section: Introductionmentioning
confidence: 99%